'Man is the Measure of All Things' - Victor Muñoz Sanz; Dan Handel (Footprint, 2019)
The term Man, and the humanist tradition which followed from it, have been challenged in feminist, queer, poststructuralist, and postcolonial critiques, which questioned its nature, or even pondered if we are actually human. What we seek in this issue of Footprint is to add to these perspectives cases of what we call radical conditioning, in which some architectures bypass assumed values of humanism and operate under a wholly different set of values, emanating from industrial and post-industrial economies and its technological developments. These architectures dictate the creation of spaces in which the human body has to operate, and to which it needs to adapt in order to survive. The research articles and visual essays included in this issue shed light on the many ways architects, advertently or inadvertently, coalesce with forces intending to condition humans. Unfolding in the study of histories, architectural types, aesthetics, atmospheres, systems, and users, authors propose inquiries along two main directions: the first trajectory highlights the prolific use in spatial design of concepts borrowed from cybernetics and information technology for the conditioning of human behavior through the built environment; the second deals with architecture conditioning the creation of new subjectivities, placing the body as the territory of intervention. Understanding these spaces, in which humans and their artifacts interact in unprecedented ways, could provide architecture with the timely opportunity to challenge our anticipated redundancy, and reconsider its own humanism in order to charge it with new meanings.